2009
DOI: 10.1007/s00239-008-9190-5
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Transposable Elements to Expressed Coding Sequence in Arabidopsis thaliana

Abstract: The goal of this study was to assess the extent to which transposable elements (TEs) have contributed to protein-coding regions in Arabidopsis thaliana. To do this, we first characterized the extent of chimeric TE-gene constructs. We compared a genome-wide TE database to genomic sequences, annotated coding regions, and EST data. The comparison revealed that 7.8% of expressed genes contained a region with close similarity to a known TE sequence. Some groups of TEs, such as helitrons, were underrepresented in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 48 publications
11
53
0
Order By: Relevance
“…Specifically the non-autonomous TEs helitrons can capture and move gene fragments and are responsible for gene duplication and conversion (Morgante et al, 2005;Hollister and Gaut, 2007). This process can even lead to the formation of novel genes (Lockton and Gaut, 2009). Although Helitrons were not identified from the littorinids, the helitron DNAREP1_DYak was the second most highly abundant TE identified in G. cineraria.…”
Section: Ce Mcinerney Et Almentioning
confidence: 99%
“…Specifically the non-autonomous TEs helitrons can capture and move gene fragments and are responsible for gene duplication and conversion (Morgante et al, 2005;Hollister and Gaut, 2007). This process can even lead to the formation of novel genes (Lockton and Gaut, 2009). Although Helitrons were not identified from the littorinids, the helitron DNAREP1_DYak was the second most highly abundant TE identified in G. cineraria.…”
Section: Ce Mcinerney Et Almentioning
confidence: 99%
“…We aimed to analyze the phylogenetic relationships of the sequence variants, and to examine the lineages of the retrotransposons. The insertion of TEs indeed changed the local genome structure and could further interfere with the expression of the nearby genes [27]. Accordingly, the active TEs mostly have deleterious effects on their host, but specific insertions can rapidly proceed to fixation, when they are beneficial [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…There are relatively few TEs within the FL-cDNA sequences compared to the genome average (TEs represent 0.32% of FL-cDNAs but >20% of GSSs), which indicates that most TEs are not expressed in P. pubescens transcriptome due to the tight regulation of TEs (Jiao and Deng, 2007). However, the presence of TEs in and around genes appears to be essential for the growth and development of the host organism (Lockton and Gaut, 2009;Pritham, 2009), because they are involved in the regulation of gene expression (Marino-Ramirez et al, 2005;Feschotte, 2008). In a seminal study, Jordan et al (2003) reported that nearly 25% of experimentally characterized human promoters contain TE sequences, including empirically defined cis-regulatory elements.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TEs may be responsible for the rate at which such incompatibility is generated in separated populations (Bennetzen, 2002). TEs are also essential components of the transcriptome during the growth and development of the host organism (Lockton and Gaut, 2009;Pritham, 2009). Transposase expression can be detected during tissue culture and growth under stress conditions, such as pathogen infection, pest infestation, drought, flooding, and exposure to radiation (Bennetzen, 2002;Jiao and Deng, 2007).…”
Section: Introductionmentioning
confidence: 99%